School experiences of Children in Need: Learning and support. (15th July 2021) - Berridge, David; Sebba, Judy; Cartwright, Mim; Staples, Eleanor
Abstract : Children in Need (CIN) have received little attention in education circles. These are children who are usually living at home but where there are concerns over their health or development due to abuse or neglect, or they are disabled. Like Children in Care (CIC, who mostly live away), educational attainments for CIN are lower than for the general pupil population, with higher levels of special educational needs. This article draws on additional analysis from a recently completed, mixed methods study into this educational attainment gap for CIN and CIC. The overall research involved quantitative analysis from official statistics of a whole‐birth cohort of children ( n  = 471, 688) born in 2000/2001 and tracked through to their General Certificate of Secondary Education exams in 2017. This was complemented by semi‐structured interviews with 18 CIN and 23 CIC, parents and associated professionals. This article focuses on interviews with CIN, their parents and professionals. Two main themes emerged from this further analysis of the qualitative data. One concerned children's problems with learning . Children said that they often struggled with their schoolwork and received insufficient classroom support to help. The second theme was that pupils and parents reported more positive experiences of learning and support in Pupil Referral Units compared with secondary schools. The overall conclusion is that attention should rightly address the social, emotional and mental health difficulties of CIN, but this should be coupled with adequate support for classroom learning.